Editorial Comment - Ahmet Mustafa (IALS Student Law Review, 2014)
In this Editorial Comment Ahmet Mustafa (Deputy Editor, ISLRev, Institute of Advanced Legal Studies) highlights the continuing relevance of international law research and suggests ways in which the journal serves jurisprudence, the science of law in its application to daily life.